Transport Costs in International Trade - Julia Spies; Joern Kleinert (European Regional Science Association (ERSA), 2011)
This paper claims that distance alone is a poor proxy for international transport costs in gravity equations. We develop a theoretical framework with a manufacturing and a transport sector, where the level of manufacturing exports determines the demand for transport. Above a certain threshold, transport service suppliers find it profit-maximizing to invest into advanced transport technology, which lowers their marginal costs and as a consequence, transport prices. Transport costs therefore vary with the distance between the two locations, and with the endogenous decision to invest in a more efficient technology. We tackle the biases in traditional gravity estimates by using newly collected data on transport prices from UPS and by applying instrument variable estimation techniques. Our results reveal that distance affects trade beyond the transport cost channel. Transport prices, in turn, are influenced by the distance and by the exports between two countries. We find that trading partners with 10% more exports enjoy 0.7% lower transport prices.
Keywords: 330